Peutz–Jeghers Syndrome which Develops into Descending Sigmoid Colon Adenocarcinoma - Abdul Mughni; Albert Eko Hendrawijaya; Meira Dewi Kusuma (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Peutz–Jeghers Syndrome (PJS) is an autosomal dominant hereditary condition mainly characterized by hamartomatous gastrointestinal (GI) polyps. Medical treatment is often sought due to complications that arise from the polyps. PJS polyps tend to be accompanied by freckling or hyperpigmentation on the lips, buccal mucosa, vulva, fingers, and toes. PJS is also associated with an increased risk for colorectal or extraintestinal tumors. Case Presentation: A 24-year-old female complained about a lump in her abdomen and constipation. The physical examination found hyperpigmentation on the lips and a hard and mobile mass on the left quadrant abdomen. We found a descending-sigmoid colon tumor with multiple polyps on all colon mucous and performed total colectomy and ileorectal anastomosis on the laparotomy operation. Two months later, Esophagogastroduodenoscopy revealed multiple polyps on Duodenum 1, II, and gaster. The colon tumor pathology result showed welldifferentiated adenocarcinoma. Conclusions: Peutz–Jeghers Syndrome (PJS) can develop into malignant intestinal tumors that require surgery for resection of the tumor.